Root Branching Is Not Induced by Auxins in Selaginella moellendorffii - Fang, Tao; Motte, Hans; Parizot, Boris; Beeckman, Tom (Frontiers in Plant Science, 2019)
Angiosperms develop intensively branched root systems that are accommodated with the high capacity to produce plenty of new lateral roots throughout their life-span. Root branching can be dynamically regulated in response to edaphic conditions and provides the plants with a soil-mining potential. This highly specialized branching capacity has most likely been key in the colonization success of the present flowering plants on our planet. The initiation, formation and outgrowth of branching roots in Angiosperms are dominated by the plant hormone auxin. Upon auxin treatment root branching through the formation of lateral roots can easily be induced. In this study, we questioned whether this strong branching-inducing action of auxin is part of a conserved mechanism that was already active in the earliest diverging lineage of vascular plants with roots. In Selaginella, an extant representative species of this early clade of root forming plants, components of the canonical auxin signaling pathway are retrieved in its genome. Although we observed a clear physiological response and an indirect effect on root branching, we were not able to directly induce root branching in this species by application of different auxins. We conclude that the structural and developmental difference of the Selaginella root, which branches via bifurcation of the root meristem, or the absence of an auxin-mediated root development program, is most likely causative for the absence of an auxin-induced branching mechanism.